1997
DOI: 10.1038/sj.onc.1201289
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Src substrate Sam68 by Cdc2 during mitosis

Abstract: Sam68 (Src-associated in mitosis) is an SH3 (Srchomology 3), SH2 (Src-homology 2), and RNA binding protein which associates with and is tyrosine phosphorylated by wild-type and activated forms of c-Src in a mitosis-speci®c manner. We now show that Sam68 immunoprecipitated from either HeLa S3 or NIH3T3 cells is phosphorylated on threonine residues exclusively during mitosis as well as on serine residues during both interphase and mitosis. Recombinant Sam68, expressed as a glutathione S-transferase (GST) fusion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 32 publications
1
45
0
Order By: Relevance
“…It was previously reported that mitotic phosphorylation of Sam68 by MPF did not alter its ability to bind synthetic RNA (Resnick et al, 1997). On the other hand, we have observed that a mild but significant phosphorylation-dependent change in RNA affinity occurs during cell cycle progression of primary spermatocytes and it is blocked by inhibition of MPF.…”
Section: Sam68 Associates With the Translational Machinerysupporting
confidence: 40%
See 1 more Smart Citation
“…It was previously reported that mitotic phosphorylation of Sam68 by MPF did not alter its ability to bind synthetic RNA (Resnick et al, 1997). On the other hand, we have observed that a mild but significant phosphorylation-dependent change in RNA affinity occurs during cell cycle progression of primary spermatocytes and it is blocked by inhibition of MPF.…”
Section: Sam68 Associates With the Translational Machinerysupporting
confidence: 40%
“…Metabolic labeling of HeLa and NIH3T3 cells with 32 P-orthophosphate highlighted a cell cycle-dependent phosphorylation of Sam68 also in serine and threonine residues. During the G1 and S phases of the cycle, Sam68 is preferentially phosphorylated in serine residues by unknown kinases, whereas during the G2/M progression it is strongly phosphorylated in threonine residues (Resnick et al, 1997). The main kinase responsible for mitotic threonine phosphorylation was MPF, although some residual activity could be ascribed to other unknown kinases.…”
Section: Sam68 Associates With the Translational Machinerymentioning
confidence: 98%
“…It has been suggested that RNA-binding functions of Sam68 positively regulate cell growth because a variant of Sam68 lacking a functional KH domain inhibits cell cycle progression (Barlat et al, 1997). Sam68 is also a direct target of Cdc2 during mitosis (Resnick et al, 1997) and an extracellular signal-regulated kinase (ERK) target (Matter et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Not only is Sam68 the only known target for Src during mitosis but it was also reported to be a target for the cyclin B/Cdc2 kinase complex that triggers mitotic progression (Resnick et al, 1997). Barlat et al (1997) demonstrated that a splice variant of Sam68 lacking most of the RNA binding KH domain was specifically expressed in quiescent cells (Barlat et al, 1997).…”
Section: Introductionmentioning
confidence: 99%